STIMULATION OF CORTISOL SECRETION BY OXYTOCIN IN CLARIAS BATRACHUS (LINN.) - NEHAR, SHAMSHUN (Journal of the Inland Fisheries Society of India, 2021)
The present work reports the modulatory role of oxytocin on cortisol secretion by the interrenal cells in Clarias batrachus. Administration of dexamethasone @ 2.5 mg kg-1 body weight and captopril @8.3 mg kg-1 body weight for seven consecutive days resulted in a sharp fall in the cortisol level from 23.82 ± 1.248 µg dl-1 to 8.9 ± 3.47 µg dl-1. Treatment with oxytocin along with the above modulators resulted in an increase in cortisol level from 8.9 ± 3.47 µg dl to 12.84 ± 0.311 µg dl. Administration of oxytocin only, in the intact fish showed a stimulatory effect on the cortical production resulting in an increase from 23.82 ± 1.248 µg dl-1 to 31.9 ± 1.173 dl-1. The data were subjected to paired sample t-test and found to be significant at 95% confidence level. The present investigation clearly indicates a stimulatory effect of oxytocin in the regulation of cortisol secretion. Key words: Cortisol, oxytocin, Clarias batrachus